114 Man-in-the-barrel syndrome as a complication of cervical decompressive surgery. (23rd August 2021) - Wijesinghe, Rajiv; Yiannikas, Con
Abstract : Objective: To present a case of painful brachial diplegia following cervical decompressive surgery. Case: A 73 year-old male presented with a 6 month history tripping over his left leg, resulting in near falls. An MRI demonstrated severe spondylotic cervical canal stenosis at C4/5 with myelomalacia and he subsequently underwent a cervical decompression and fusion at this level. On post-operative day five he developed severe pain in his neck and shoulders and mild weakness of his left arm. One week later he underwent a second operation with decompression and rhizolysis at C5 to C8. On post-operative day 3 he awoke with severe pain similar to previously, followed a day later by profound weakness of all movements around the shoulders bilaterally, but movements around the elbows, wrists and fingers were normal. While walking his arms hung limply beside him, giving him the appearance of a man in a barrel. Routine nerve conduction studies and median somatosensory evoked potentials were normal. Eelectromyography confirmed denervation within the C5 myotome bilaterally, however with selective sparing of the rhomboids bilaterally. This suggested a lesion distal to the branch to rhomboids, and a diagnosis of bilateral post-operative brachial neuritis was made. Conclusion: Acute proximal arm weakness is an uncommon complication of cervical surgeries, referred to commonly as a post-operative C5 palsy. Investigations performed in this case however suggest that a brachial plexus lesion may be the cause of this peculiar syndrome. This syndrome may lie on the spectrum of post-surgical inflammatory neuropathies.